Biochars from olive mill waste have contrasting effects on plants, fungi and phytoparasitic nematodes - Marra, Roberta; Vinale, Francesco; Cesarano, Gaspare; Lombardi, Nadia; d’Errico, Giada; Crasto, Antonio; Mazzei, Pierluigi; Piccolo, Alessandro; Incerti, Guido; Woo, Sheridan L.; Scala, Felice; Bonanomi, Giuliano (PLOS ONE, 2018)
Olive mill waste (OMW), a byproduct from the extraction of olive oil, causes serious environmental problems for its disposal, and extensive efforts have been made to find cost-effective solutions for its management. Biochars produced from OMW were applied as soil amendment and found in many cases to successfully increase plant productivity and suppress diseases. This work aims to characterize biochars obtained by pyrolysis of OMW at 300 °C to 1000 °C using 13C NMR spectroscopy, LC-ESI-Q-TOF-MS and SEM (Scanning Electron Microscopy). Chemical characterization revealed that biochar composition varied according to the increase of pyrolysis temperature (PT). Thermal treated materials showed a progressive reduction of alkyl C fractions coupled to the enrichment in aromatic C products. In addition, numerous compounds present in the organic feedstock (fatty acids, phenolic compounds, triterpene acids) reduced (PT = 300 °C) or completely disappeared (PT ≥ 500 °C) in biochars as compared to untreated OMW. PT also affected surface morphology of biochars by increasing porosity and heterogeneity of pore size. The effects of biochars extracts on the growth of different organisms (two plants, one nematode and four fungal species) were also evaluated. When tested on different living organisms, biochars and OMW showed opposite effects. The root growth of Lepidium sativum and Brassica rapa, as well as the survival of the nematode Meloidogyne incognita, were inhibited by the untreated material or biochar produced at 300 °C, but toxicity decreased at higher PTs. Conversely, growth of Aspergillus, Fusarium, Rhizoctonia and Trichoderma fungi was stimulated by organic feedstock, while being inhibited by thermally treated biochars. Our findings showed a pattern of association between specific biochar chemical traits and its biological effects that, once mechanistically explained and tested in field conditions, may lead to effective applications in agriculture.